Phổ hấp thụ electron của một số phức chất của nguyên tố đất hiếm với axit DL-2-amino-n-butyric - Kiên, Lê Chí; Thanh Lê, Đặng Thị; Roãn, Phạm Đức (Vietnam Journal of Chemistry, 2014)
The electronic spectrum of some rare earth complexes with DL-2-amino-n-butyric acid have been recorded in the 400 ÷ 1100 nm region in water. It was found that the DL-2-amino-n-butyric acid utilized amino nitrogen and carboxyl oxygen for bonding